Numerical Seismic Performance Evaluation of Fixed-Base Essential Data Centers in Indonesia - Arif Rusyana; Yuskar Lase (PT. Global Research Collaboration, 2026)
The development of data center facilities in Indonesia has increased significantly over the past decade, driven by the escalating demand for cloud storage and the rapid growth of electronic transactions requiring large-scale data capacities. However, Indonesia's location on the Pacific Ring of Fire poses critical challenges regarding the earthquake resilience of these facilities. The Telecommunications Industry Association (TIA-942-C, 2024) standard stipulates a higher performance level for Rated III and Rated IV data centers, requiring continuous post-earthquake operations and the incorporation of passive protective devices such as base isolators or viscous dampers. In contrast, the Indonesian national standard (SNI 8799-1, 2023) classifies these structures at a minimum as Risk Category III buildings, without requiring additional passive protection systems. This paper presents a comparative study of fixed-base data center models, focusing on overall building performance and seismic resilience. Information Technology (IT) equipment, particularly hard disk drives (HDDs), is highly sensitive to floor accelerations that exceed permitted thresholds. To assess this, two 4-story fixed-base data center models, designed under Risk Category II and Risk Category IV provisions, were evaluated using Nonlinear Time-History Analysis (NLTHA), which represented performance levels below and above the provisions of SNI 8799-1 (2023). The findings indicate that the strengthened model complying with Risk Category IV demonstrated an average reduction in roof drift of 42% and a corresponding average increase in base shear of 6%. This improved the structural performance level to Life Safety (LS), although the target performance at the level is Immediate Occupancy (IO) for Rated IV facilities. However, the increased structural stiffness inherently amplified the roof peak floor acceleration (PFA) by an average of 34%, resulting in PFA values that significantly exceeded the safety threshold for digital data storage media. Consequently, both structural models fail to satisfy post-earthquake operational conditions and pose a potential risk to digital data integrity following an -level seismic event.